Trauma in Otolaryngology - Das, Jayita (Springer Singapore, 2018)
Trauma is an important aspect of all clinical care specialties. As a rule, each specialty has its own approaches to and protocols for dealing with trauma. This book focuses on the various aspects of trauma in ENT for all groups of practitioners - students, trainees and independent professionals alike - and provides an essential guide to the optimal management of ENT trauma.